O esporte como conteúdo da educação física no ensino fundamental : uma abordagem multirreferencial - Câmara, Eduardo Cavalcante (2020)
The school formation process is mainly related to the learning of several sabers, which should contribute to the formation of the subject at school. These sabers are organized into disciplines, each of which, although maintaining relations with each other, carries their specificities. Among these disciplines, there is physical education, a curricular component of basic education that, among other aspects, addresses knowledge of the body in moviment, which are comprised in an área called “body culture of movements” (BRASIL, 1998). This area adds knowledge such as the game, Sport, dances, fights, rhythmic and expressive activities, among others. Among this knowledge, Sport emerges as the one that hás perhaps been the most worked in this discipline. However, what seems to have been prioritized in his approach is the treatment with na almost exclusive emphasis on technical knowledge. We do not want to deny the importance of this knowledge, however, closing ourselves to this perspective is to limit the learning possibilities that this knowledge can provide. Considering these aspects, we started to think about the possibilities of treating this knowledge beyond a reductionist perspective. In our considerations, we look at the multi-referencial approach, which can be considered a paradgimatic perspective of seeing and thinking about the reality, considering the mutiplicity of views that surrounds it, which is essential to the development of a subject formation. From these reflections, our starting question emerged, which gained the following wording: is it possible a pedagogical practice for teaching aports based on multi-referentiality? From this question, we built our objective, which is to analyze the pedagogical treatment os sport in school from the multirreferencial approach, seeking to identify if this practice contributes to the development of the plural look and to the strengthening of students’ authorship. Perspective us, ths, propose na approach that makes it possible to work on Sport as contento f the discipline, which can give the student a greater and better perception of the world, since it allows the approximation to reality, identifying the multiple elements that compose it – such as social, cultural and biological aspects – which makes it freer from social determinations, especially those based on monological perspectives, in addition to the institution of authorship. This work was carried out through the action research proposal, in which the researcher is directly involved and undoubtedly involved in the researched object. For data collection, we Will use three research instruments: research journal, questionnaire with open questions and evaluation forms. In this way,the work made it possible to verify that a large parto f the students managed – from the multiple references provided during the intervention process – to acquire a new look about the contents. Such a look, generated from different types of knowledge, contributed to a greater and better understanding of the content, in addition to allowing some students the ability to Express themselves from their own authorship, thus perceiving themselves as actors and authors their own actions, productions and thoughts.